Emergency care assessment tool for health facilities: a validity study in Cameroon - Kim, Paul (Division of Emergency Medicine, 2019)
Background To date, health facilities in Sub-Saharan Africa have not had an objective measurement tool for evaluating comprehensive emergency service provision. One major obstacle is the lack of consensus on a standardised evaluation framework, applicable across a variety of resource settings. The African Federation for Emergency Medicine (AFEM) developed an assessment tool specifically for these settings - the Emergency Care Assessment Tool (ECAT) - that assesses provision of key medical interventions. These interventions are referred to as signal functions for the six sentinel conditions that occur prior to death: respiratory failure, shock, altered mental status, severe pain/trauma, and dangerous fever. A signal function represents the culmination of knowledge of interventions, supplies, and infrastructure capable for the management of an emergent condition. Previous studies aimed at the refinement and context modification of the ECAT have already been performed in multiple African countries. We undertook a validation study to help determine the applicability of the tool in assessment of emergency services throughout the continent. Aims and Objectives The aim of this study was to determine the content, construct, and face validity of the AFEM Emergency Care Assessment Tool in Cameroon. To achieve this, the study had the following objectives: (1) Employ the ECAT in district, regional, and central hospitals in Cameroon. (2) Use direct observation to determine whether the signal functions can be performed in these facilities. Methods This was an observational study at a convenience sample of five hospitals in Cameroon: three district, one regional, and one central. The goal of this study was to validate the instrument, not the facility, and so the sample size was related to the number of signal functions witnessed rather than the number of facilities visited. The tool was administered with the Head of Emergency at each facility. This completed ECAT was then compared with direct observations of the signal functions, a process which was conducted by the partner local emergency care specialists accompanied by the ECAT researcher. Results In general, the higher the level of facility, the greater the emergency care capacity and the greater the number of signal functions that could be performed correctly and consistently. Discrepancies in funding, supplies, resource allocation, and care delivery ability were apparent through ECAT results, expounding on barriers to care delivery, and direct observation. McNemar tests on the ECAT results versus direct observation at each facility yielded statistically significant support for tool validation at the national level emergency unit as well as two of the district level emergency units. Concordance between reported and observed signal functions could not be achieved at the regional facility and one of the district facilities. Conclusions The ECAT has good potential for facility level assessment of emergency care provision, and collects meaningful information that can guide effective improvements in the delivery of emergency care.